“I discovered race in America and it fascinated me”: Alienation, Exile and the Discovery of Cultures in Chimamanda Ngozi Adichie’s Americanah - Rezaie, Ali (American Studies in Scandinavia, 2021)
Depicting the economic and cultural problems facing its Nigerian immigrant protagonists, Chimamanda Ngozi Adichie’s novel, Americanah provides a great opportunity for its readers to understand the increasing appeal of the idea of cultures among immigrants in the West. It shows how the problems accompanying cultural dislocation compel even alienated individuals who previously idealized the West to embrace their cultures and move away from universal and individualistic perspectives such as liberalism. Cultural dislocation not only helps immigrants discover the importance and particularity of their own culture but also the continuing influence of cultures in the West. Further complicating the picture, however, the novel also reveals how the culture discovered by immigrants in exile is distinctly different from the culture lived and understood by their counterparts in their native country. By frankly depicting both the cultural problems facing African immigrants in a racialized America and the prevalence and negative effects of Eurocentric cultural alienation among non-Western youth, Americanah helps us understand the surprising turn to cultures and away from liberalism at the start of the twenty-first century.